DICTION AND IMAGINATION: HOW WORDS SHAPE THE WORLD IN POETRY - Adi Nurhadi; Mochamad Sanwasih (GoAcademica Research dan Publishing, 2026)
This research aims to analyze the interaction between word choice (diction) and psychological processes (imagination) in constructing an autonomous reality in poetry. The main problem examined is how a specific typology of diction can stimulate the reader's sensory imagery, thus successfully forming a complete new world ecosystem within the text. The method used in this research is descriptive qualitative with a stylistic analysis approach. The research data, in the form of words, phrases, and lines of poetry, were collected through listening and note-taking techniques using a corpus of poetry text data from several works by canonical Indonesian poets. The results show that the intensive use of connotative diction and concrete words acts as a linguistic stimulus that activates visual, auditory, tactile, and kinesthetic imagery within the reader's cognition. Through the accumulation of these sensory stimuli, the collaboration between diction and imagination successfully constructs an autonomous reality (a new world) within the text. This new world possesses its own logical sovereignty, where the physical laws of the universe, the dimensions of space, and the elasticity of time can be completely deconstructed and reconstructed to achieve a complete aesthetic truth.